New Culture Turns One Hundred: A Centennial Reflection on the May Fourth and New Culture Movement in Singapore - Kenley, David (Translocal Chinese: East Asian perspectives (Online), 2022)
Abstract Centennial commemorations of the May Fourth Movement in Singapore demonstrate how practices of remembrance reinforce but also transcend national and cultural boundaries. Throughout 2019, Singaporeans reflected on the iconoclastic, anti-imperialist, and pro-democracy elements of May Fourth while simultaneously challenging public memories as observed in China. As such, these commemorations shed important light on memory studies, postcoloniality, and Singapore Chinese identity.